Review of the concentration, bioaccumulation, and effects of lanthanides in marine systems - Patricia Neira; Patricia Neira; Ana Romero-Freire; Ana Romero-Freire; María Dolores Basallote; Hao Qiu; Antonio Cobelo-García; Carlos Ruiz Cánovas (Frontiers in Marine Science, 2022)
Rare earth elements (REEs) or lanthanides are often found together in nature, and they are used in multiple anthropogenic activities from green energy and medical technologies to telecommunications and defense systems. However, the current understanding on the concentration and behavior of REEs in oceans and marine organisms is limited, and no regulatory information or limits have been settled. Here, we present a review of the concentrations of lanthanides in marine waters and biota. REEs reach aquatic ecosystems mainly by continental contributions, and the maximum reported concentrations of REEs are found on the platform surface near the coast due to their continental origin. For coastal waters, we find maximum REE levels in the surface water that decrease with depth until a certain stability. Their concentrations diminish as they move toward the open ocean, where concentrations tend to increase vertically with depth in the water column. Only cerium (Ce) showed different patterns from other REEs caused by Ce different redox states: III and IV, reflecting the oxidation of dissolved Ce (III) to particulate Ce (IV) when reacting with the O2 to form CeO2. In seawater, heavy REEs tend to remain in solution forming complexes usually unavailable for organisms, while light REEs are most likely to be assimilated by them, posing potential biological implications. Bioaccumulation of REEs decreases as marine trophic level increases, showing a trophic dilution pattern. Generally, higher concentrations are found in organisms such as phytoplankton, zooplankton, and algae species, while the lowest concentrations are found in mollusks, corals, and fish species. According to the current trend in the REE industry, the increasing anthropogenic emissions are a fact; therefore, more studies will be needed regarding their fractionation, the transformation processes with which they become bioavailable, and their pathways in marine systems.